Scientific-Social-Community Impacts: The Study on Micro Drones and Nano Drones - Rekha P. ,; Asuti , Manjunath G.; Hussain, Maaz; Naveed, Misrah (Science and Technology - Recent Updates and Future Prospects Vol. 5, 2024)
This study aims to consolidate and discuss the diverse applications of drone technology across various domains, including defense, agriculture, indoor exploration, forest navigation, swarm robotics, disaster management, and waste assessment. This study encompasses a comprehensive analysis of research explorations spanning different applications of drone technology, focusing on the methodologies employed, major findings, and implications in respective fields. The study also covers research conducted in diverse geographical locations and spans varying durations, reflecting the global significance and ongoing advancements in drone technology. Various methodologies encompassing experimental validation, algorithm development, field trials, and simulations to address specific challenges in each application domain are discussed. Drone technology presents versatile solutions across diverse domains, revolutionizing practices in agriculture, exploration, disaster management, and environmental monitoring. Continued research and innovation are crucial for unlocking the full potential of drones and ensuring their widespread adoption for societal benefit.